The effectiveness of targeted therapy for recurrence or metastasis adenoid cystic carcinoma: a systematic review and meta-analysis - Lu Zhang; Hao-Nan Yang; Ying Wang; Dan Li; Zheng Lei; Meng-Qi Yang; Yun-Chang Liu; Jiang He; Yong-Zhong Wu; Jiang-Dong Sui (Annals of Medicine, 2024)
Background and purpose Several clinical studies have demonstrated the potential of molecular-targeted agents for the treatment of recurrent or metastatic adenoid cystic carcinoma (R/M ACC). However, there is currently no consensus regarding the efficacy of molecular-targeted agents for patients with R/M ACC. This study aimed to evaluate the therapeutic efficacy and safety of molecular-targeted agents in patients with R/M ACC and provide insights to guide clinical decision-making.Materials and methods Five databases (PubMed, Embase, Cochrane, ProQuest, and Scopus) were searched based on the search strategy and selection criteria. Primary endpoints were objective response rate (ORR) and progression-free survival (PFS). The secondary endpoints were disease control rate (DCR), overall survival (OS), metastatic sites, and adverse events (AE). Pooled estimates were calculated using a random-effects meta-analysis.Results Finally, 28 studies, involving 849 patients, were included. The most common metastatic sites were the lungs, bones, liver, lymph nodes, and kidneys. The pooled ORR was 4.0% (95% CI, 0.7–8.8%), the pooled DCR was 80.5% (95% CI, 72.2%–87.7%). Compared with other-target drugs, multiple kinase inhibitors (MKIs) improved the ORR (pooled ORR for single-target drugs vs. MKIs: 5.9% vs. 0%). The combination of MKIs and immune checkpoint inhibitors (ICIs) had a significantly higher ORR (17.9% in the axitinib + avelumab group). The pooled median PFS and OS were 8.35 and 25.62 months, respectively. MKIs improved the median PFS compared to other-target drugs (9.43 months vs 5.06 months). In addition, the most common adverse events (AEs) were fatigue (51.6%), hypertension (44.2%), and nausea (40.0%), followed by hand-foot skin syndrome (36.8%), diarrhoea (34.4%), weight loss (34.2%), anorexia (31.8%), rash (31.7%), and headache (29.0%).Conclusion The findings of this study suggest that MKIs have a better therapeutic efficacy than single-target drugs in patients with R/M ACC. Future studies are warranted to verify the synergistic role of the combination strategy of MKIs plus ICIs, given the limited number of studies on this topic conducted and published to date.